The ameliorative effect of selenium-loaded chitosan nanoparticles against silver nanoparticles-induced ovarian toxicity in female albino rats - Omnia E. Shalaby; Yasmine H. Ahmed; Aya M. Mekkawy; Mohamed Y. Mahmoud; G. A. Elbargeesy (Journal of Ovarian Research)
Abstract Background Recently, silver nanoparticles (Ag-NPs) were shown to provoke oxidative stress through the release of reactive oxygen species and consequently induce cell damage. Selenium-loaded chitosan nanoparticles (CS-SeNPs) have anti-inflammatory and antioxidant effects, indicating that they ameliorate Ag-NPs-induced ovarian toxicity. Objective This study aimed to assess how well CS-SeNPs counteract the damaging effects of Ag-NPs on the ovarian tissue of adult female albino rats. Methods Forty mature female albino rats were divided into four equal groups: for 60 days, Group I (control) was given 0.5 ml/kg of distilled water; Group II was given Ag-NPs orally (100 mg/kg); Group III was given Ag-NPs orally (100 mg/kg/d) plus CS-SeNPs (0.5 mg/kg/d); and Group IV was given only CS-SeNPs orally (0.5 mg/kg/d). All the ovarian tissues were removed and underwent immunohistochemical, histological, and biochemical analyses. Results Ag-NPs-exposed rats revealed a marked reduction in reduced glutathione (GSH) and superoxide dismutase (SOD). Numerous histopathological alterations were found along with a significant increase in PCNA- and Caspase-3-immunoreactive cells. Most of these alterations were successfully ameliorated by CS-SeNPs, as indicated by marked increases in GSH and SOD. Conclusion CS-SeNPs ameliorate the toxic effects of Ag-NPs on the ovarian tissue of adult female albino rats.